Pengembangan Aplikasi Perangkat Bergerak Sistem Informasi dan Manajemen Bank Sampah Kota Batu berbasis Android (Studi Kasus: Bank Sampah Teratai Putih) - Ian Setyo Aji; Agi Putra Kharisma; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Garbage is a waste product that is produced from the rest of human activities every day. The volume of waste generated by local residents and tourists in Batu City every day can reach 99 tons. In achieving the waste reduction target, the Environment Service invites the public to apply the 3R principles. Teratai Putih Waste Bank is a place for the people of Batu City to deposit waste that is still of value. However, data recording at the Teratai Putih waste bank in Batu City has several obstacles, for example difficulties in searching data, and it takes a lot of time to record customer data. The data recording was done manually using a book. The current business process is considered to be lacking in time efficiency, so a new business process is needed. This research develops Android-based software that can help perform data recapitulation related to waste bank management at the Teratai Putih Waste Bank. The SDLC used in developing software is SDLC Prototyping. In terms of effectiveness, managers get a success rate of 90% in carrying out their duties while customers get a success rate of 94%. Furthermore, on the aspect of efficiency, the results of obtaining efficiency time for managers can complete their tasks by 0.030 every second. Meanwhile, customers can complete their tasks by 0.055 per second. In addition, the proposed business process is 35.8% faster than the current business process.